The Eco-Driving Behaviour: A Strategic Way to Control Tailpipe Emission - Arokiaraj, Dr; R. Srivel, Mr; R.Arthie Reena, Ms (International Journal of Engineering and Technology, 2018)
The global auto industry is responsible for 15.9% of carbon emission (OICA) and among that, vehicle users are responsible for around 80% of carbon emission (JAMA). Awareness about environmental problems caused by this emission is rapidly increasing among people and governments are organizing various campaigns to make people familiar with the eco-driving concept. Vehicle users do not realize that their driving style has a direct influence on fuel consumption and this, in turn, leads to unwanted carbon emission. Therefore, there is a need to understand the car users' eco-driving behavior and explores the awareness level of passenger car users. Data has been collected from 400 respondents through the help of a structured questionnaire with a focus on eco-driving behavior practices. Analysis of this data showed that the pressure given to accelerate the engine is transformed into tailpipe emission. Therefore, this study highlights the importance of inculcating eco-driving behavior among car users in particular and vehicle users in general.Â Â